Giulio Maspero, Rethinking the Filioque with the Greek Fathers, William B. Eerdmans Publishing Company, Grand Rapids, Michigan 2023, pp. 326 - Przyszychowska, Marta (Vox Patrum, 2023)
A review of the book: Giulio Maspero, "Rethinking the Filioque with the Greek Fathers, William B. Eerdmans Publishing Company, Grand Rapids, Michigan 2023.